2020
DOI: 10.1002/humu.24068
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of novel rapidly mutating Y‐chromosomal short tandem repeat markers

Abstract: Short tandem repeat polymorphisms on the male‐specific part of the human Y‐chromosome (Y‐STRs) are valuable tools in many areas of human genetics. Although their paternal inheritance and moderate mutation rate (~10−3 mutations per marker per meiosis) allow detecting paternal relationships, they typically fail to separate male relatives. Previously, we identified 13 Y‐STR markers with untypically high mutation rates (>10−2), termed rapidly mutating (RM) Y‐STRs, and showed that they improved male relative differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
46
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 64 publications
(171 reference statements)
9
46
1
2
Order By: Relevance
“…Thus, for differentiation of father-son pairs, analysing more RM Y-STRs with CE seems to be a much more promising approach than just sequencing the common Y-STRs. Recently, Ralf et al proposed 12 new RM Y-STRs with a mean mutation rate of 2.6 × 10 −2 , demonstrating high discrimination power [34]. We also agree with Huszar et al that applying MPS to RM Y-STRs is expected to increase discriminatory power as allele diversity increases.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Thus, for differentiation of father-son pairs, analysing more RM Y-STRs with CE seems to be a much more promising approach than just sequencing the common Y-STRs. Recently, Ralf et al proposed 12 new RM Y-STRs with a mean mutation rate of 2.6 × 10 −2 , demonstrating high discrimination power [34]. We also agree with Huszar et al that applying MPS to RM Y-STRs is expected to increase discriminatory power as allele diversity increases.…”
Section: Discussionsupporting
confidence: 89%
“…Mutations were observed at all types of markers, including simple and complex repeat structures and trimeric to hexameric repeat structures. Our results suggest that tetranucleotide repeats are more prone to mutations than other motifs [32][33][34], mutation events are mostly restricted to the LUS of a compound/complex STR marker [31,32,34,35], and the LUS length correlates with the mutability of an STR marker [32][33][34][36][37][38]. Unsurprisingly, when looking at the sequence variants between unrelated males, we found that the observed length variance is mainly explained by changes in the repetitive structure of a Y-STR.…”
Section: Discussionmentioning
confidence: 66%
“…Arwin Ralf et al. [11] applied a newly developed in silico search approach to the Y‐chromosome reference sequence, and highlighted 12 novel RM Y‐STRs in Europe. It is one of the efficient ways to strengthen the capacity of RM Y‐STR system for differentiating relative or unrelated males.…”
Section: Discussionmentioning
confidence: 99%
“…In general, forensic DNA analysis seeks individual identification [11]. Male relative differentiation using Y‐chromosome markers has been achieved by rapidly mutating Y‐STRs, which are termed RM Y‐STRs [12,13], with mutation rates ( μ ) > 10 –2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation